Pengembangan UMKM Melalui Diferensiasi Produk Pada UMKM Bakso Dan Es Campur "Family" Di Kota Blitar - Muhammad Ghulam Dzaki Abdillah; Niniek Imaningsih; Cholid Fadil (Transformasi: Journal of Economics and Business Management, 2023)
UMKM is a business that is often found in all corners of Indonesia, including the city of Blitar. In Blitar City itself there are many types of UMKMs engaged in each field. Not a few UMKMs are engaged in the same field and have similar product results. Of course this creates competition. Business actors need to have a strategy so that the UMKMs they have can still develop and not lose many consumers. One way is by making product differentiation. The methods used by the executors are interviews and market surveys to analyze existing problems and conditions. Then brainstorm to find a solution. Cheese meatballs are the final decision made in the implementation of product differentiation at the UMKM Bakso dan Es Campur “Family”. With this product differentiation, it is hoped that the UMKM concerned will have its own charm compared to its competitors.